Pulsatile tinnitus - Case report of duralarteriovenous fistula and review of the literature - Monteiro, Daniel (2014)
Tinnitus is defined has being a conscientious sensation of noise, without an external stimulation. Although tinnitus is not considered a disease, many patients suffer from this symptom. It has many different etiologies, but only a few are known. Vascular malformations are the main cause of pulsatile tinnitus. We describe two cases of patients presenting with pulsatile tinnitus. Both patients were submitted to a magnetic resonance angiogram that diagnosed a dural arteriovenous fistula of the right lateral sinus, one with a type I and another with a type IIa Cognard fistula. A cerebral angiography was performed and the embolization of the fistulas was achieved by the use of polyvinyl alcohol particles and Onyx®. The treatment of dural arteriovenous fistulas should be pondered in depending on the type of fistula, according to the Cognard or Borden Classification systems and if symptoms exist or not.